STAPHYLOCOCCAL SPECIES RESPONSIBLE FOR BOVINE MASTITIS IN KHARTOUM STATE, SUDAN - Rabie Mohammed Salih, Reem; Osman Ahmed, A/ Basit (Journal of Veterinary Medicine and Animal Production, 2022)
This study was conducted in certain area at Khartoum State (Eltebna, Falasteen, Shambat, Hilat Kuku, Elhalfaia, Elsamrab and The University of Khartoum farms) from May/2006 to April/2008 to determine the type of Stapylococcus spps which cause bovine mastitis. The total number of dairy cows, which were examined in 34 investigated farms, amounted to 500 animals. The infected cows with mastitis were found in all investigated farms. The percentages of acute mastitis caused by Staph aureus and Staph hyicus amounted to 24% and the percentage of chronic mastitis caused by Staph aureus was 44% and that caused by Staph hyicus was 8%.